2011
DOI: 10.1007/s00296-011-1958-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of physical activity in reducing pain in patients with fibromyalgia: a blinded randomized clinical trial

Abstract: The purpose of this study was to evaluate and compare the effectiveness of muscle-strengthening exercises (MS) and a walking program (WA) in reducing pain in patients with fibromyalgia. Ninety women, 30-55 years of age, diagnosed with fibromyalgia according to the American College of Rheumatology 1990 criteria, were randomized into 3 groups: WA Group, MS Group, and control group. Pain (visual analog scale) was evaluated as the primary outcome. Physical functioning (Fibromyalgia Impact Questionnaire, FIQ), heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
1
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 23 publications
5
95
1
9
Order By: Relevance
“…It is a rather common condition as its worldwide average prevalence is estimated 2.7 % in the general population, with a greater prevalence in women (4.1 %) than in men (1.4 %) [2]. Fibromyalgia affects many aspects of daily life and has serious personal and social implications [3,4].Though the treatment for fibromyalgia is still controversial, current evidence strongly suggests that the most effective intervention combines physical exercise, pharmacological treatment, and cognitive-behavioral therapy [5]. More specifically, it has been demonstrated that physical exercise is highly beneficial in (1) the management of pain; (2) the reduction in stiffness, fatigue, and depression; and (3) the adoption by patients of a more positive attitude toward the disease [6][7][8].…”
mentioning
confidence: 99%
“…It is a rather common condition as its worldwide average prevalence is estimated 2.7 % in the general population, with a greater prevalence in women (4.1 %) than in men (1.4 %) [2]. Fibromyalgia affects many aspects of daily life and has serious personal and social implications [3,4].Though the treatment for fibromyalgia is still controversial, current evidence strongly suggests that the most effective intervention combines physical exercise, pharmacological treatment, and cognitive-behavioral therapy [5]. More specifically, it has been demonstrated that physical exercise is highly beneficial in (1) the management of pain; (2) the reduction in stiffness, fatigue, and depression; and (3) the adoption by patients of a more positive attitude toward the disease [6][7][8].…”
mentioning
confidence: 99%
“…Thus, increasing tissue oxygenation as a result of aerobic exercise could potentially diminish peripheral and central sensitization and reduce clinical pain (3). The exercise-induced endogenous opioid activity in the central and peripheral nervous system (37) could also partially justify pain reductions observed following exercise programs in FM (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…We considered these covariates, as they are known potential confounders of the association under study (23)(24)(25). Because there is evidence suggesting that improving physical fitness might reduce pain (3,4), each pain-related outcome was treated as a dependent variable, and physical fitness measurements as independent variables, in all the analyses.…”
Section: Significance and Innovationsmentioning
confidence: 99%
See 2 more Smart Citations